Aseptic Necrosis of the Femoral Head Developing After Covid-19 Disease (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Long COVID-19’ can affect different body systems. At present, avascular necrosis (AVN) as a sequalae of ‘long COVID-19’ has yet not been documented. By large-scale use of life-saving corticosteroids in COVID-19 cases, we anticipate that there will be a resurgence of AVN cases. We report a series of three cases in which patients developed AVN of the femoral head after being treated for COVID-19 infection. The mean dose of prednisolone used in these cases was 758 mg (400–1250 mg), which is less than the mean cumulative dose of around 2000 mg steroid, documented in the literature as causative for AVN. Patients were symptomatic and developed early AVN presentation at a mean of 58 days after COVID-19 diagnosis as compared with the literature which shows that it generally takes 6 months to 1 year to develop AVN post steroid exposure. This article is made freely available for use in accordance with BMJ’s website terms and conditions for the duration of the covid-19 pandemic or until otherwise determined by BMJ. You may use, download and print the article for any lawful, non-commercial purpose (including text and data mining) provided that all copyright notices and trade marks are retained.